How Rewards Influence the Link Between Organizational Commitment and Whistleblowing Intentions? - Benediktus Bayu Adiprana; Ranto Pratomuan Sihombing (LP3M Universitas Putra Bangsa, 2025)
A person's intention to whistleblow can be influenced by several factors, namely ethics, moral intensity, personal cost, professional identity, and organizational commitment. This study focuses on knowing the effect of the moderating variable reward on the relationship between organizational commitment and intention to whistleblow. The research type is quantitative, using primary data obtained through questionnaires. Purposive sampling was used as a sampling technique. The sample amounted to 101 respondents who were permanent employees at large/medium furniture manufacturing companies in Central Java. The questionnaire was processed with SPSS version 21. MRA was used to analyze the interaction of moderating variables in the study. The results showed that organizational commitment has a positive effect on whistleblowing intention, while reward is not a moderating variable for the relationship between organizational commitment and whistleblowing intention.